INCREASING THE ACTIVENESS AND LEARNING OUTCOMES OF MATHEMATICS ON THE MATERIAL OF MATHEMATICAL SENTENCES AND CALCULATIONS THROUGH THE REALISTIC MATHEMATIC EDUCATION (RME) APPROACH FOR GRADE IV STUDENTS OF SDN 2 CEPEDAK - Yanti; Muflikhul Khaq; Rintis Rizkia Pangestika3 (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Improving the Activeness and Learning Outcomes of Mathematics on Mathematical Sentences and Calculations Through the Realistic Mathematic Education (RME) Approach for Grade IV Students of SDN 2 Cepedak